Recent Global Patterns in Prostate Cancer Incidence and Mortality Rates - Culp, MaryBeth B.; Soerjomataram, Isabelle; Efstathiou, Jason A.; Bray, Freddie; Jemal, Ahmedin (European urology, 2020)
Previous studies have reported significant variation in prostate cancer rates and trends mainly due to differences in detection practices, availability of treatment, and underlying genetic susceptibility. To assess recent worldwide prostate cancer incidence, mortality rates, and trends using up-to-date incidence and mortality data. We present estimated age-standardized prostate cancer incidence and mortality rates by country and world regions for 2018 based on the GLOBOCAN database. We also examined rates and temporal trends for incidence (44 countries) and mortality (76 countries) based on data series from population-based registries. The highest estimated incidence rates were found in Australia/New Zealand, Northern America, Western and Northern Europe, and the Caribbean, and the lowest rates were found in South-Central Asia, Northern Africa, and South-Eastern and Eastern Asia. The highest estimated mortality rates were found in the Caribbean (Barbados, Trinidad and Tobago, and Cuba), sub-Saharan Africa (South Africa), parts of former Soviet Union (Lithuania, Estonia, and Latvia), whereas the lowest rates were found in Asia (Thailand and Turkmenistan). Prostate cancer incidence rates during the most recent 5 yr declined (five countries) or stabilized (35 countries), after increasing for many years; in contrast, rates continued to increase for four countries in Eastern Europe and Asia. During the most recent 5 data years, mortality rates among the 76 countries examined increased (three countries), remained stable (59 countries), or decreased (14 countries). As evident from available data, prostate cancer incidence and mortality rates have been on the decline or have stabilized recently in many countries, with decreases more pronounced in high-income countries. These trends may reflect a decline in prostate-specific antigen testing (incidence) and improvements in treatment (mortality). We examined recent trends in prostate cancer incidence and mortality rates in 44 and 76 countries, respectively, and found that rates in most countries stabilized or decreased. We examined recent trends in prostate cancer incidence and mortality rates in 44 and 76 countries, respectively, and found that rates mostly stabilized or decreased. These trends may reflect declines in prostate-specific antigen testing (incidence) and improvements in treatment (mortality).